Numerical simulation of the flow through an intermittent gas lift valve - Concho, Maria A.; Gasbarri, Sandro; Rojas-Solorzano, L. (Proceeding of ETCE/OMAE2000 Joint Conference Energy for the New Millenium February 14-17, 2000, New Orleans, LA, 2000)
The numerical simulation of the flow through a pilot valve used in the oil intermittent gas lift process is presented.The complexity of the non-isothermal compressible flow is modeled by the solution of the Navier-Stokes, Mass Conservation and Energy equations for the compressible flow. Numerical results and analyses pertaining to the flow dynamics through a 1½-inch pilot valve at an operating condition encountered in typical field operations are presented
Keywords: Research Subject Categories::TECHNOLOGY::Engineering mechanics; mechanical engineering; Numerical simulation of the flow